RELIGIOUS STRENGTHENING IN CYBER SPACE BETWEEN INDONESIA AND PAKISTAN - Nawawi, Muhammad Latif; Andrianto, Dedi; Kurniawan, Wakib; Al Ayyubi, Ibnu Imam; Sain, Zohaib Hassan (SYAIKHONA: Jurnal Magister Pendidikan Agama Islam, 2025)
This study examines the strengthening of religious values in cyberspace in Indonesia and Pakistan two countries with the world’s largest Muslim populations and significant influence on contemporary Islamic discourse. The rapid advancement of digital technology and the widespread use of social media have created new arenas for religious transmission, especially among younger generations who are deeply engaged in online communication. In Indonesia, platforms such as YouTube, Instagram, and TikTok are extensively used by preachers to convey Islamic teachings in creative, simplified, and engaging formats, reflecting an approach rooted in Islamic moderation (Wasathiyah). In contrast, in Pakistan, digital preaching has also flourished but tends to adopt a more conservative tone and operates under stricter government regulation due to historical sectarian tensions and concerns about extremist influence. Employing a qualitative approach with interactive analysis techniques, this study investigates the roles of governments, religious institutions, and civil society in shaping religious narratives within digital spaces. The findings reveal that while both countries acknowledge the transformative potential of cyberspace for promoting religious education and identity formation, they also face persistent challenges such as radicalization, misinformation, and online hate speech. Consequently, the study underscores the importance of strengthening digital religious literacy and fostering collaborative regulatory frameworks to ensure that cyberspace evolves into an inclusive, constructive, and peaceful environment for reinforcing Islamic values. These insights contribute to broader academic discussions on religion, media, and the transformation of Islamic education in the digital age.